Основні риси кам’янської культури Східного Криму - Кислий, О.Є. (Археологія, 2006)
У статті підсумовано результати вивчення пам’яток типу поселення Кам’янка Східного Криму. Показано шляхи формування і розвитку кам’янської культури, а також ЇЇ особливості. Еще в 30—40 гг. прошлого века исследователи (П.М. Заболоцкий, О.М. Бадер, О.Я. Брюсов), познакомившиеся с
памятниками каменского типа (более позднее определение В.Д. Рыбаловой), считали возможным говорить об отдельной археологической культуре. С.Н. Братченко объединял в единую группу каменско-ливенцовские поселения
Крыма и нижнего Дона. Накопление полевых материалов и их анализ (В.Д. Рыбалова, В.А. Колотухин, А.Е. Кислый,
Г.Н. Тощев) послужили основой для изучения своеобразия процессов развития местного населения Восточного и
Юго-Восточного Крыма в XVIII —XV вв. до н. э. Керамические комплексы свидетельствуют о связях каменской
культуры с катакомбной, а также о переживании традиций периода бытования ямной и кеми-обинской культур,
близости культуры многоваликовой керамики; находки в целом свидетельствуют о разнонаправленных контактах,
что совпадает с концепцией формирования подвижного социума культуры многоваликовой керамики. As early as in the 1930-40s the researchers (P.M. Zabolotskiy, O.M. Bader, O.Ya. Bryusov) who took a closer look at the
Kam’janske type monuments (later definition by V.D. Rybalova) could refer to an individual archaeological culture. S.N. Bradchenko
combined Kam’janske-Liventsovo settlements of Crimea and Lower Don River Region into one group. Accumulation
of field materials and their analyses (V.D. Rybalova, V.A. Kolotukhin, A.E. Kislyi, G.N. Toshchev) formed a basis for the
study of the variety of processes of development of local population at the Eastern and Southeastern Crimea in the XVIII -
XV cc. BC. Ceramics assemblages speak in favor of ties between the Kam’janske culture and the catacomb culture, as
well as of surviving traditions dating from the time of the Pit Grave and Kemi-Oba cultures, similarity of the poly-cordon
ceramics culture; the finds as a whole testify to diverse contacts what agrees with the concept of formation of a mobile
society of the poly-cordon ceramics culture.